Fabrication of CdTe QDs/BiOI-Promoted TiO2 Hollow Microspheres with Superior Photocatalytic Performance Under Simulated Sunlight - Xiaofei Qu; Meihua Liu; Longfei Li; Chunqi Wang; Cuihua Zeng; Jianhuang Liu; Liang Shi; Fanglin Du (Nanoscale Research Letters, 2019)
Abstract Hollow and heterostructured architectures are recognized as an effective approach to improve photocatalytic performance. In this work, ternary TiO2/CdTe/BiOI with hollow structure was constructed via a step-by-step method. In addition, the effect of TiO2 structural regulation and the energy band alignment of BiOI and CdTe quantum dots (CdTe QDs) with TiO2 in TiO2/CdTe/BiOI on photocatalytic dye removal were also studied. The results reveal that the TiO2/CdTe/BiOI heterostructures with hollow substrates exhibit much higher photocatalytic activities than pure TiO2, P25, TiO2/CdTe, and TiO2/BiOI and ternary TiO2/CdTe/BiOI with solid substrates. For TiO2(H)/CdTe/BiOI, several synergistic factors may be responsible for the remarkable visible-light photodegradation performance, such as strong visible-light absorption by BiOI and larger specific surface area.